Generasi Sehat, Bebas Karang Gigi : Edukasi dan Pencegahan Karang Gigi pada Remaja di Desa Bilalang Gowa - Suciyati Sundu; Faradillah Usman; Dewi Sartika3; Dwi Rezky Aulyah; Pariati Pariati (Compromise Journal Community Proffesional Service Journal, 2025)
Tartar is a common oral health problem among adolescents. Tartar forms from hardened plaque due to a lack of proper and regular brushing habits. If not treated early, this condition can lead to serious disorders such as gingivitis (gum inflammation) and periodontitis (damage to the supporting tissue of the teeth), which impact adolescents' quality of life and self-confidence. Therefore, education about the dangers of tartar and the importance of maintaining oral health is essential, especially in schools. This community service activity aims to increase adolescents' knowledge and awareness of the dangers of tartar and equip them with proper toothbrushing skills. The activity was held on July 5, 2025, at SMP Negeri 1 Manuju, Bilalang Village, Gowa Regency, and was attended by seventh and eighth grade students. The methods used included interactive education, simulations of toothbrushing techniques according to health standards, and the distribution of leaflets as additional information that students can access again. Evaluation was carried out through pre- and post-tests to measure knowledge gains, as well as direct observation of toothbrushing practices. The results of the activity showed a significant increase in students' knowledge scores, namely 31.3 points (from an average of 53.4 to 84.7). Furthermore, 92% of students were able to practice correct toothbrushing techniques. These results indicate that an educational approach combined with simulations and visual media is effective in increasing understanding and changing clean and healthy lifestyle behaviors in adolescents. This activity is expected to become a model for sustainable dental health education in schools and be replicated elsewhere.